2017
DOI: 10.3390/su9040614
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas and Air Pollutant Emissions of China’s Residential Sector: The Importance of Considering Energy Transition

Abstract: This study focuses on China's residential sector and examines energy use growth resulting from income increases and urbanization development. We also look at the energy transition (from primitive fuels to advanced fuels) caused by economic development, as well as the mitigation potential of greenhouse gas and air pollutants emissions. Several studies have provided evidence of a positive correlation between income and per capita final energy use at the national level. In addition to income, demographic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…The singular pursuit of emission reduction or abatement cost reduction is not conducive to supporting both environmental quality and economic development. In addition, due to the homologous nature of air pollutants and greenhouse gases, optimizing the energy structure is the key to achieve collaborative governance in the long-term [7,18]. However, only a few articles have discussed emission reduction schemes from the perspective of energy consumption, and these studies have not also considered the abatement costs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The singular pursuit of emission reduction or abatement cost reduction is not conducive to supporting both environmental quality and economic development. In addition, due to the homologous nature of air pollutants and greenhouse gases, optimizing the energy structure is the key to achieve collaborative governance in the long-term [7,18]. However, only a few articles have discussed emission reduction schemes from the perspective of energy consumption, and these studies have not also considered the abatement costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While previous studies have been devoted to the collaborative governance of air pollutants and greenhouse gases in the context of technological improvements and macro control, in the long run, the energy structure, which is the ratio between one energy type consumption and the total energy consumption [6], holds the key to achieving collaborative governance [7]. The main air pollutants of China such as SO 2 , and NO X , and greenhouse gas CO 2 are produced from the consumption of fossil fuel-based energy sources, including coal, oil, and natural gas, which also offer the potential for collaborative governance [8].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Lavaine (2015) included socio-economic characteristics to explore the relationship between air pollution and mortality rates. In another study by Xing et al (2017), it was found that income, education and household size are major drivers of energy transition in the residential sector and therefore have an impact on air pollution, while other studies found that female share in households has an impact on household energy choice in Bolivia, Guatemala and some Asian countries (Sathaye and Tyler ;Israel, 2002;Heltberg, 2005;Gupta and Kohlin, 2006). Based on the literature we presented so far we include in our regression estimates the most important socio-economic factors.…”
Section: Datamentioning
confidence: 99%
“…When cooking with a gas stove, harmful gases such as carbon monoxide and formaldehyde are released because of incomplete combustion. The harmful gases emitted from a gas stove adversely affect the human body, so it is necessary to ensure continuous ventilation even during cold winters, and the hood must be cleaned frequently [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%